2+3(x+1)=9-3+2x

Simple and best practice solution for 2+3(x+1)=9-3+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+3(x+1)=9-3+2x equation:


Simplifying
2 + 3(x + 1) = 9 + -3 + 2x

Reorder the terms:
2 + 3(1 + x) = 9 + -3 + 2x
2 + (1 * 3 + x * 3) = 9 + -3 + 2x
2 + (3 + 3x) = 9 + -3 + 2x

Combine like terms: 2 + 3 = 5
5 + 3x = 9 + -3 + 2x

Combine like terms: 9 + -3 = 6
5 + 3x = 6 + 2x

Solving
5 + 3x = 6 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
5 + 3x + -2x = 6 + 2x + -2x

Combine like terms: 3x + -2x = 1x
5 + 1x = 6 + 2x + -2x

Combine like terms: 2x + -2x = 0
5 + 1x = 6 + 0
5 + 1x = 6

Add '-5' to each side of the equation.
5 + -5 + 1x = 6 + -5

Combine like terms: 5 + -5 = 0
0 + 1x = 6 + -5
1x = 6 + -5

Combine like terms: 6 + -5 = 1
1x = 1

Divide each side by '1'.
x = 1

Simplifying
x = 1

See similar equations:

| 4(x+7)=-2x+34 | | x^3+8x^2+20x=0 | | 8x^2+5x+25=0 | | 5x+2=14+6X | | 13(17-x)=15(x+1) | | -7(1-2x)+8=-83 | | g(x)=3(5)x | | 4r^2-r+3=0 | | 3v+6=9-3(2v-2) | | x+3(x+6)=4(2x+1) | | 4(3z-3)=18 | | (2x-17)/5=-5 | | -11=3(v-7)-8v | | 13+x+2x=6x+1 | | 4x^2+8x+36=0 | | 73/100=81 | | 4x+4+8+2x=3(x+5) | | 3u^2+17u+24=0 | | 4x+6(x+2)=35 | | (5x-3)/9=-2 | | 2/3x5/6x14x18 | | -8(3x+1)-4=11 | | 3000(x+100)=2000(x-100) | | -4-8y=35 | | 2(x-5)(x+4)=0 | | 2x-5+8x=7-4x-12 | | 2(14+2x)=8(2+x) | | 2•1/3•3.14•25•25•25 | | 2u^2+15u+28=0 | | 4x+9x-34=68-4x | | -14=-3x | | 3x+7=5x+1-x |

Equations solver categories